Mariano García, María José Punte y María Lucía Puppo (comp.). Espacios, imágenes y vectores. Desafíos actuales de las literaturas comparadas. Buenos Aires: Miño y Dávila, 2015. 256 pp. ISBN 978-84-16467-02-0. - Serber, Daniela C. (2016)
Fil: Serber, Daniela C.. Universidad del Salvador